Beef Cattle Feed Efficiency in Badung Regency - Astiti, Ni Made Ayu Gemuh Rasa; Rukmini, Ni Ketut Sri; Rejeki, I Gusti Ayu Dewi Seri (Journal of Agriprecision & Social Impact, 2024)
This research is a literature study of marketing efficiency. This research aims to analyze the marketing efficiency of beef cattle in Badung. The method used in this research is qualitative research with field research techniques, namely direct observation of the object being studied to obtain relevant data. This research was carried out in Badung with the types of data used in this research, namely primary data and secondary data. The results of the research concluded that the feed efficiency of beef cattle in smallholder livestock businesses in Badung is low.